Incremental method engineering with modeling tools : theoretical principles and empirical evidence - Tolvanen, Juha-Pekka (1998)
The main objective of this study is to improve the applicability of information system development (ISD) methods supported by modeling tools. This is carried out by examining and extending method engineering (ME) processes. To draw on an analogy with software engineering, ME develops and improves ISD methods. Instead of introducing a set of standardized methods in an ISD project, we assume that its method requirements vary. ISD projects differ greatly and are more situation-bound than is usually assumed. We suggest that methods should be constructed according to the needs of particular ISD situations and contingencies. To continue the analogy, just as software engineering is guided by ISD methods, ME is guided by (meta)methods. In order to develop ISD methods and improve their flexibility we develop methodical guidelines that are founded on engineering principles. These guidelines specify how knowledge related to methods should be described, analyzed, and maintained for ISD projects, and how it should be adapted into ISD tools. The topic of ME is important, since local method development is common in organizations, and there is a lack of knowledge about the development and use of local methods. In this thesis we focus on incremental ME. Any organization that builds ISs not only delivers systems, it also learns and creates knowledge about how to carry out ISD, and thus crafts new ISD methods. An incremental approach aims to make this experience systematic, leading to continuous method improvement. Accordingly, methods are a part of organizational knowledge which evolves and needs to be maintained in an organization. This thesis puts forward three principles of incremental ME. First, constructs of method modeling languages for carrying out efficient incremental ME are described. Second, guidelines and mechanisms for collecting and analyzing modeling-related experiences are defined, and their implications for method improvements are explained. Third, the viability of the principles proposed is demonstrated in two cases of incremental ME. The resulting ME principles can be applied in organizations which are developing their own method and need methodical guidelines for this task.